Power flow control in single-phase and three-phase grid-connected inverters using LMI, state-feedback linearization and D-stability - Sampaio, Leonardo Poltronieri; De Brito, Moacyr Aureliano Gomes [UNESP]; De Azevedo E Melo, Guilherme [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper proposes a methodology for the active and reactive power flow controls, applied at singlephase and three-phase inverters operating in grid-connected mode at low voltage. The converter's control technique is based on Linear Matrix Inequalities (LMI) together with D-stability criteria and state-feedback linearization. The power flow control uses the power transfer curves (similarly to droop control) P-ω e Q-V, applied to a multi-loop control system. The multi-loop control uses the technique of state-feedback linearization in order to minimize the non linearities of system, improving the controller's performance and mitigating potential system's disturbs. Moreover, the purpose of the methodology is to obtain the best controllers with the lowest gains placing the poles in the left-half s-plane region specified during the design stage, resulting in fast responses with reduced oscillations. Finally, a 1000VA single-phase and one 3000VA three-phase prototypes were implemented in order to demonstrate the feasibility of the proposed control. © 2013 IEEE.
Keywords: Alternative energy; Converter Control; Distributed Power; Microgrid; Robust Control